2014
DOI: 10.1155/2014/352420
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Purification of a New P-I Class Metalloproteinase fromBothrops moojeniVenom with Antiplatelet Activity

Abstract: The present study aimed to evaluate the proteolytic and biological activities of a new metalloproteinase from B. moojeni venom. The purification of BmooMPα-II was carried out through two chromatographic steps (ion-exchange and affinity). BmooMPα-II is a monomeric protein with an apparent molecular mass of 22.5 kDa on SDS-PAGE 14% under nonreducing conditions. The N-terminal sequence (FSPRYIELVVVADHGMFTKYKSNLN) revealed homology with other snake venom metalloproteinases, mainly among P-I class. BmooMPα-II cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
1
11
0
1
Order By: Relevance
“…The enzyme CK is an important marker of muscle injury because it is at high plasma levels under these conditions, in view of its extravasation from the intracellular environment (muscle cells) to the extracellular (blood) environment. Thus, our results showed high plasma concentrations of CK in the first hours (3 hours; Figure A) after BmooTX‐I consistent with the results of Santos‐Filho et al and with previous data on muscle damage caused by B. moojeni venom when injected to animals . According to Santos‐Filho et al, optical and electron microscopy analysis revealed that BmooTX‐I was able to cause severe myonecrosis accompanied by inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The enzyme CK is an important marker of muscle injury because it is at high plasma levels under these conditions, in view of its extravasation from the intracellular environment (muscle cells) to the extracellular (blood) environment. Thus, our results showed high plasma concentrations of CK in the first hours (3 hours; Figure A) after BmooTX‐I consistent with the results of Santos‐Filho et al and with previous data on muscle damage caused by B. moojeni venom when injected to animals . According to Santos‐Filho et al, optical and electron microscopy analysis revealed that BmooTX‐I was able to cause severe myonecrosis accompanied by inflammatory infiltrate.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our results showed high plasma concentrations of CK in the first hours (3 hours; Figure 5A) after BmooTX-I consistent with the results of Santos-Filho et al 22 and with previous data on muscle damage caused by B. moojeni venom when injected to animals. 60 According to Santos-Filho et al, 22 optical and electron microscopy analysis revealed that BmooTX-I was able to cause severe myonecrosis accompanied by inflammatory infiltrate. The gastrocnemius muscle fibres were extensively destroyed presenting different stages of degeneration and oedema.…”
mentioning
confidence: 99%
“…Platelet aggregation assays were performed in PRP and measured using the automated Aggregometer 4 channels (AggRAMTM version 1.1, Helena Laboratories, USA) as described by Queiroz et al [ 16 ]. Human blood, collected in the presence of sodium citrate (3.2%), was centrifuged at 100× g for 12 min at room temperature to obtain PRP.…”
Section: Methodsmentioning
confidence: 99%
“…The imbalance of the hemostatic system is the most studied biological effect caused by these toxins (Markland Jr and Swenson, 2013;Ramos and Selistre-De-Araujo, 2006;Takeda et al, 2012). They can interfere in platelet aggregation and in the coagulation cascade, causing pro-or anti-coagulant effects (Camacho et al, 2014;Gutiérrez and Rucavado, 2000;Queiroz et al, 2014;Sajevic et al, 2011;Takeda et al, 2012).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…jararacussu (Marcussi et al, 2007), atroxlysin-I from B. atrox (Sanchez et al, 2010), BmooMPα-II from B. moojeni (Queiroz et al, 2014), and barnettlysin-I (Bar-I) from B. barnetti (Sanchez et al, 2016). The enzymatic activity of these PI SVMPs is critical for significant inhibition of platelet function.…”
Section: Accepted Manuscriptmentioning
confidence: 99%